ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN SEKTOR PERTANIAN DI KABUPATEN SUMBAWA - Suprianto, S; Zulkia, Andipta Ahmad (Pusat Riset dan Publikasi, 2025)
This study aims to know the potential and development strategies of the agricultural sector in Sumbawa District. The type of this study was descriptive with a quantitative approach. The type of data used in this study was quantitative obtained directly from primary sources. The numbers of informants were 7 informants consisted of 1 main informant and 6 key informants. Data analysis in this study used Location Quotient (LQ) and SWOT analysis techniques. The results of this study showed that the agricultural sector in Sumbawa District had great potential that has not been optimally utilized. The result of LQ analysis showed that several agricultural sub-sectors in Sumbawa district had significant comparative advantages compared to the same sub-sectors at the provincial level. The contribution of the agricultural sector to the GRDP of Sumbawa district during the 2019-2023 period showed significant trend but was not yet optimal. The main strength factors were wide of agricultural area and crop diversity that could be cultivated. However, the weaknesses were the limited of capital and agricultural technology. The development strategy recommended were increasing access to get capital and technology, strengthening agricultural institutions, and increasing human resource capacity through training and education. The implementations of these strategies were expected to optimize the potential of the agricultural sector, improve farmer welfare, and had contribution significantly to the economic growth of Sumbawa district.